Seismic performance of reinforced concrete frame with lead viscoelastic damper under mainshock-aftershock sequences. (July 2022) - Huang, Weiyuan; Shi, Fei; Zhang, Chao; Zhou, Yun; Li, Zheng
Abstract: This study proposes a strategy of utilizing novel lead viscoelastic damper (LVD) to improve the seismic performance of the weakened reinforced concrete (RC) frame under mainshock-aftershock sequences. The working mechanism and mechanical behavior of the LVD were experimentally investigated through cyclic loading tests. A six-story LVD frame was designed to have similar structural characteristics to the original RC frame and modeled in OpenSees. Incremental dynamic analyses were carried out on both RC frame and LVD frame under mainshock only scenario and mainshock-aftershock sequences. The mainshock and aftershock seismic performance of the LVD frame and RC frame was assessed at various damage states. Results show that the developed LVD characterizes by high effective stiffness, excellent damping capacity, low-frequency sensitivity, and stable hysteretic performance. Although with weakened RC components, the LVD frame still has about 25.1% higher median PGA demands than the RC frame at various mainshock damage states, indicating that the LVD system plays a significant role in enhancing the mainshock seismic performance of the RC frame. The aftershock IDA results confirm that thanks to the excellent damping capacity of the LVD, the weaker RC frame with LVD systems outperforms the original RC frame by about 21.08%, 10.59%, and 13.33% in median aftershock PGA demands, aftershock collapse capacity, and residual aftershock collapse capacity, respectively.